Design, Synthesis, and Assessment of Tricarboxylic Acid Cycle Probes - Chen, Joseph; Chao, Darrian; Tran, Uyen Phuong; Billingsley, Kelvin L. (Synthesis, 2024)
Hyperpolarized 13C magnetic resonance spectroscopy can provide unique insights into metabolic activity in vivo. Despite the advantages of this technology, certain metabolic pathways such as the tricarboxylic acid (TCA) cycle are more challenging to examine due to the limitations associated with currently available hyperpolarized 13C probes. In this report, we systematically employ computational analyses, synthetic techniques, and in vitro studies to facilitate the design of new chemical probes for the TCA cycle. This platform allows for the rapid identification of probe scaffolds that are amenable to hyperpolarized 13C experimentation. Using these results, we have developed two 13C-labeled chemical probes, [1,4-13C2]-dipropyl succinate and [1,4-13C2]-diallyl succinate, which are employed in hyperpolarized 13C metabolic studies.
Keywords: hyperpolarized 13C; chemical probe; metabolism; tricarboxylic acid cycle; esterification; esterase; in vitro assays